1987
DOI: 10.1136/bjsm.21.1.18
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maximum steady state pace training on running performance.

Abstract: Maximum aerobic power (V02 max), maximum anaerobic power (AP max), submaximal exercise heart rate (HRsub), and performance times for distances of 15m, 600m, 3.22km, and 10km were evaluated in 12 male runners prior to and after 7 weeks of a running programme at each individual's maximum steady-state (MSS) pace. MSS pace, a runnning speed at which blood lactate is believed to equal 2.2 mmol.l-1, was calculated from weekly 3.22 km runs utilising the regression equation of LaFontaine et al (1981). During the train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…The actual training data presented here in endurance athletes showing that 1) low-intensity training accounts for the majority of training time and 2) there is an association between total cumulative training time at low intensities (zone 1) and endurance performance during events held at very high intensities (i.e., 30 min at Ͼ85% V O 2max ) are in apparent disagreement with some classic studies showing that physiological or performance improvements are associated with high-intensity training sessions (8,39). Steadypace sessions at an intensity of at least 80 -90% V O 2max (i.e., approximately RCT) have traditionally been considered to be the optimal intensity based on the results from previous studies (30,39). Furthermore, one distinguishable feature of the best endurance runners of the modern era (i.e., East Africans) is the high intensity of their training sessions, as mentioned above, although this trend is not evident in the data from Billat et al (4).…”
Section: How Do Runners Train?mentioning
confidence: 96%
“…The actual training data presented here in endurance athletes showing that 1) low-intensity training accounts for the majority of training time and 2) there is an association between total cumulative training time at low intensities (zone 1) and endurance performance during events held at very high intensities (i.e., 30 min at Ͼ85% V O 2max ) are in apparent disagreement with some classic studies showing that physiological or performance improvements are associated with high-intensity training sessions (8,39). Steadypace sessions at an intensity of at least 80 -90% V O 2max (i.e., approximately RCT) have traditionally been considered to be the optimal intensity based on the results from previous studies (30,39). Furthermore, one distinguishable feature of the best endurance runners of the modern era (i.e., East Africans) is the high intensity of their training sessions, as mentioned above, although this trend is not evident in the data from Billat et al (4).…”
Section: How Do Runners Train?mentioning
confidence: 96%
“…However, it has also been pointed out that the variation of • VO2max cannot always explain running performance in subjects with a limited range of performance levels (Conley and Krahenbuhl, 1980;Sjödin and Svedenhag, 1985). Recent researches have shown that the ability to run without accumulating lactate as a fatigue substance in active muscles is more critical than the magnitude of • VO2max (Fay et al, 1989;Grant et al, 1997;Heck et al, 1985;Priest and Hagan, 1987;Sjödin and Jacobs, 1981;Sjödin and Svedenhag, 1985;Urhausen et al, 1993;Yoshida et al, 1990Yoshida et al, , 1993. These researchers have recommended some blood lactate-related indices, such as lactate threshold (LT), maximal lactate steady state (maxLass), and onset of blood lactate accumulation (OBLA) to evaluate longdistance running performance, because the metabolic acidosis can be kept constant if the exercise intensity is established based on the information about blood lactate concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies reporting HR,,,, the values given probably originate from common Vo2 , , , tests. A specific HR,,, procedure is seldom described (5,6,8,12,13). The standard criteria normally used to assure that Vo, is achieved are usually not adequate to assure that HR,,, is achieved.…”
Section: Fig 5 the Relation Between Peak Hrmentioning
confidence: 99%
“…Many studies reporting measurement of HR,,, do not describe a specific HR,,, test procedure (5-11). Often the given HR,,, values originate from registration obtained during maximal oxygen uptake tests (12,13).The, aim of this study was to investigate the influence of warm-up, time and number of runs, angle on the treadmill and importance of being rested to assess HR,,, during running. Furthermore, peak HR from field and laboratory testing have been compared.…”
mentioning
confidence: 99%
See 1 more Smart Citation